2015
DOI: 10.1371/journal.pone.0132320
|View full text |Cite|
|
Sign up to set email alerts
|

Self-Knowledge Dim-Out: Stress Impairs Metacognitive Accuracy

Abstract: Modulation of frontal lobes activity is believed to be an important pathway trough which the hypothalamic-pituitary-adrenal (HPA) axis stress response impacts cognitive and emotional functioning. Here, we investigate the effects of stress on metacognition, which is the ability to monitor and control one's own cognition. As the frontal lobes have been shown to play a critical role in metacognition, we predicted that under activation of the HPA axis, participants should be less accurate in the assessment of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 38 publications
(54 reference statements)
7
45
0
1
Order By: Relevance
“…[20][21][22] Metacognition is impacted by stress, with acute stress correlating with less accurate assessment of performance. 23 Pharmacy and other college students are often under huge amounts of stress from heavy course loads and nonacademic-related pressures. While this study was conducted in a low-stakes fashion, the same is not true of college courses.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Metacognition is impacted by stress, with acute stress correlating with less accurate assessment of performance. 23 Pharmacy and other college students are often under huge amounts of stress from heavy course loads and nonacademic-related pressures. While this study was conducted in a low-stakes fashion, the same is not true of college courses.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of results may suggest a unique neurobiological mechanism for the 485 interaction of stress, memory, and metacognition. One recent study by Reyes et al (2015) tested 486 individual response to stress induction, and then at a later date participant's perceptual 487 metacognitive ability. These authors found that high-stress responders showed an altered 488 overall level of confidence and reduced metacognitive ability.…”
Section: Mediation Results -Auditory Memory and Metacognition 397mentioning
confidence: 99%
“…Studies often try to get around the trait desirability influence by using third person vignettes, and/or scenarios where admitting a psychiatric problem brings the protagonist some kind of (financial) benefit. Despite this way around, however, in the 5 For a good account of holding subjective beliefs that give meaning and enable our "cultural" existence, and exist in the paradox of simultaneously not to be questioned but also not to be imposed on the others, see (36 (38) show that stress in the form of interpersonal challenge decreases metacognitive sensitivity. 7 See, for example, Bowles and Sharman (39) and Perlman et al (40) on the effects of using leading interview questions in court with vulnerable adults.…”
Section: Compliance With the Assessment Relationshipmentioning
confidence: 99%